Antibody cross-reactivity and evidence of susceptibility to emerging Flaviviruses in the dengue-endemic Brazilian Amazon. (April 2023) - Salgado, Barbara Batista; Maués, Fábio Carmona de Jesus; Jordão, Maele; Pereira, Renato Lemos; Toledo-Teixeira, Daniel A.; Parise, Pierina L.; Granja, Fabiana; Souza, Higo Fernando Santos; Yamamoto, Marcio Massao; Chiang, Jannifer Oliveira; Martins, Livia Caricio; Boscardin, Silvia Beatriz; et al.
Highlights: Over 75% of adult individuals had antidengue antibodies in the city of Manaus. Dengue virus-positive individuals do not cross-neutralize zika virus efficiently. Varying degree of cross-reactivity against emerging and endemic Flaviviruses. Abstract: Objectives: Several Flaviviruses can co-circulate. Pre-existing immunity to one virus can modulate the response to a heterologous virus; however, the serological cross-reaction between these emerging viruses in dengue virus (DENV)-endemic regions are poorly understood. Methods: A cross-sectional study was performed among the residents of Manaus city in the state of Amazonas, Brazil. The serological response was assessed by hemagglutination inhibition assay (HIA), enzyme-linked immunosorbent assay, and neutralization assay. Results: A total of 74.52% of the participants were immunoglobulin G-positive (310/416), as estimated by lateral flow tests. Overall, 93.7% of the participants were seropositive (419/447) for at least one DENV serotype, and the DENV seropositivity ranged between 84.8% and 91.0%, as determined by HIA. About 93% had antiyellow fever virus 17D-reactive antibodies, whereas 80.5% reacted to wild-type yellow fever virus. Zika virus (ZIKV) had the lowest seropositivity percentage (52.6%) compared with other Flaviviruses. Individuals who were DENV-positive with high antibody titers by HIA or envelope protein domain III enzyme-linked immunosorbent assay reacted strongly with ZIKV, whereas individuals with low anti-DENV antibody titers reacted poorly toward ZIKV. Live virus neutralization assay with ZIKV confirmed that dengue serogroup and ZIKV-spondweni serogroup are far apart; hence, individuals who are DENV-positive do not cross-neutralize ZIKV efficiently. Conclusion: Taken together, we observed a high prevalence of DENV in the Manaus-Amazon region and a varying degree of cross-reactivity against emerging and endemic Flaviviruses. Epidemiological and exposure conditions in Manaus make its population susceptible to emerging and endemic arboviruses.